The Psychological Well-Being of Mothers Raising Deaf-Mute Children: A Qualitative Case Study - Asharayya Mulia Izzati; Siti Nur Asiyah (International Conference on Sustainable Health Promotion, 2025)
This study explores the psychological well-being of a mother raising a deaf and mute child. Using a qualitative single case study with in-depth interviews, findings were analyzed thematically based on Ryff’s six dimensions of psychological well-being. Results show that the mother demonstrated self-acceptance through emotional regulation, built positive relationships with family and community, maintained autonomy in parenting decisions, managed her environment by balancing household and caregiving, pursued life goals by focusing on health and her child’s future, and experienced personal growth through improved emotional maturity and learning sign language. These findings highlight the importance of family support, community involvement, and self-development in fostering maternal psychological well-being.